1999
DOI: 10.1056/nejm199904293401702
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of the Aortic Root in Patients with Marfan's Syndrome

Abstract: Elective aortic-root replacement has a low operative mortality. In contrast, emergency repair, usually for acute aortic dissection, is associated with a much higher early mortality. Because nearly half the adult patients with aortic dissection had an aortic-root diameter of 6.5 cm or less at the time of operation, it may be prudent to undertake prophylactic repair of aortic aneurysms in patients with Marfan's syndrome when the diameter of the aorta is well below that size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
308
2
18

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 583 publications
(333 citation statements)
references
References 17 publications
5
308
2
18
Order By: Relevance
“…If the maximal cross-sectional area in square centimeters of the ascending aorta or root divided by the patient's height in meters exceeds a ratio of 10, surgical repair is reasonable because shorter patients have dissection at a smaller size and 15% of patients with Marfan syndrome have dissection at a size smaller than 5.0 cm. 42,47,48 (Level of Evidence: C)…”
Section: Class Imentioning
confidence: 99%
“…If the maximal cross-sectional area in square centimeters of the ascending aorta or root divided by the patient's height in meters exceeds a ratio of 10, surgical repair is reasonable because shorter patients have dissection at a smaller size and 15% of patients with Marfan syndrome have dissection at a size smaller than 5.0 cm. 42,47,48 (Level of Evidence: C)…”
Section: Class Imentioning
confidence: 99%
“…4 The optimal medical therapy for aortic root dilation has been a matter of vigorous debate.17 -22 Because several, though not all, studies have shown that therapy with beta-adrenergic blocking drugs (BB) reduces the rate of aortic growth,17 -20 many clinicians consider BB to be the standard of care. The presumed mechanisms, decreasing proximal aortic shear stress and heart rate, are plausible based on the pathophysiology; however, treatment with BBs does not prevent attainment of important clinical endpoints including aortic regurgitation, surgery, dissection, and death.…”
Section: Current Medical Approach To Aortic Root Dilation In Mfsmentioning
confidence: 99%
“…2 Up to 90% of individuals with classic MFS will have a cardiovascular "event" during their lifetime, including surgical repair of the aortic root, fatal or non-fatal aortic dissection, or mitral valve surgery. 3,4 In addition, individuals with MFS may have lens dislocation; skeletal involvement including anterior chest deformity, scoliosis, and joint hypermobility; lung disease most commonly manifested by spontaneous pneumothorax; decreased skeletal muscle mass and fat stores; and dural ectasia. 1 …”
Section: Introduction the Marfan Syndrome (Mfs)mentioning
confidence: 99%
“…Na síndrome de Marfan, existe concordância de que a correção cirúrgica profilática esteja indicada quando o diâ-metro atinge 5,5cm, embora este valor possa ser menor (4,5 a 5cm) em pacientes com história familiar de dissecção, ruptura ou morte súbita 23,111,[128][129][130][131][132] . Nos demais casos, embora a presença de sintomas ou a severidade da insuficiência aórtica possa indicar intervenção independente das dimensões da aorta, é aceito geralmente o diâmetro de 6cm como indicativo de cirurgia em aneurismas assintomáticos 23,133 .…”
Section: Aorta Acendente -Arco Aórticounclassified